Tinjauan Yuridis Pertanggungjawaban Mutlak (Strict Liability) dalam Hukum Perlidungan Konsumen - Putu Rido Widiya Widnyana; Anak Agung Istri Agung; Ni Gusti Ketut Sri Astiti (Warmadewa Press, 2021)
Consumers become objects of business activities to gain large profits. Stiff, consumers' position towards producers is not balanced because consumers are weak, so consumers need to get legal protection. Business actors often respond to events that harm consumers by cornering consumers and looking for consumer weaknesses. The method used in this writing uses nonnative legal research, namely examining problems using a regular basis in statutory regulations and supported by scholars' opinions in the literature. It is essential to explore the principle of absolute liability(strict liability)in consumerprotectionlaw and the provisionsof business actors' strict liabilityto consumers'protectionlaw. As for the conclusion, there is the principle of absolute liability (strict liability) in consumer protection law, namely that business actors are obliged to compensatefor the loss of goods and servicesthat consumers have purchasedforlosses sufferedby consumers, and if the business actor does negligence and failure to consumers can be given sanctions as stipulated in Law No. 8 of 1999 concerning consumer protection